2014
DOI: 10.1002/chem.201405380
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Culture Medium Stability, and In Vitro and In Vivo Zebrafish Embryo Toxicity of Metal–Organic Framework Nanoparticles

Abstract: Metal–organic frameworks (MOFs) are among the most attractive porous materials available today. They have garnered much attention for their potential utility in many different areas such as gas storage, separation, catalysis, and biomedicine. However, very little is known about the possible health or environmental risks of these materials. Here, the results of toxicity studies on sixteen representative uncoated MOF nanoparticles (nanoMOFs), which were assessed for cytotoxicity to HepG2 and MCF7 cells in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
165
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(182 citation statements)
references
References 67 publications
(95 reference statements)
7
165
0
Order By: Relevance
“….) In this sense, a second work dealing with the a Laboratoire de Cancérologie Expérimentale, Service de Radiobiologie screening of the in vivo toxicity of nine nanoMOFs with different structures and compositions in zebrafish embryos was recently reported by Ruyra et al, 28 concluding a wide variation of the toxicity of the different nanoMOFs and highlighting the influence of the cation leaching coming from the hybrid network degradation. [19][20][21][22][23][24] Therefore, prior to any bioapplication of nanoMOFs, it is of high relevance to investigate their toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
“….) In this sense, a second work dealing with the a Laboratoire de Cancérologie Expérimentale, Service de Radiobiologie screening of the in vivo toxicity of nine nanoMOFs with different structures and compositions in zebrafish embryos was recently reported by Ruyra et al, 28 concluding a wide variation of the toxicity of the different nanoMOFs and highlighting the influence of the cation leaching coming from the hybrid network degradation. [19][20][21][22][23][24] Therefore, prior to any bioapplication of nanoMOFs, it is of high relevance to investigate their toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
“…Many animal models have been used to test NPs embryo-toxicity; these include zebrafish [28, 10, 11, 1417, 2022, 2428, 31, 33, 35, 37, 38, 41, 43, 4547, 4951, 5357, 59, 62, 64, 6670], mice [1, 9, 12, 13, 42, 48, 52, 63, 71], rat [18, 19, 30, 32], chicken [36, 44], oryzias latipes [23, 29, 34, 58], Xenopus laevis [7, 60], sea urchin [40] Mytilus galloprovincialis (Lmk) [39], snail [61], and oyster [65]. Many different types of NPs have been tested using these animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Many different types of NPs have been tested using these animal models. The most popular NPs are silver (Ag) NPs [1, 3, 8, 12, 13, 16, 2226, 28, 32, 33, 34, 37, 38, 41, 43, 48, 49, 55, 56, 65, 66, 70], then zinc oxide (ZnO) NPs [3, 7, 14, 15, 1820, 26, 40, 47, 62], gold (Au) NPs [3, 29, 30, 45, 46, 5052, 55, 66, 67], titanium dioxide (TiO2) NPs [9, 16, 17, 21, 25, 28, 31, 39, 63, 69], silicon dioxide (SiO2) NPs [3, 26, 35, 58, 63], Cd NPs [3, 26, 53, 61], chitosan NPs [4, 42, 57], quantum tots [11, 60, 68], Cu NPs [25, 27, 64], platinium (Pt) NPs [44, 55] and other NPs including CoFe2O4, selenium, diamond, Ni, F2O3, and lead NPs [2, 5, 6, 10, 26, 27, 36, 45, 54, 59, 69, 71]. Although many articles have been published exploring the embryo-toxicity of NPs, only their toxic effects on different embryos have been investigated and very few studies have examined the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that other factors such as formation of new species upon degradation, nature of crystals (e.g., size, shape, charge, etc.) may also contribute to toxicity of nanoscale MOFs (Ruyra et al 2015). There are many other parameters that may contribute toward toxicity of nanoscale MOFs, e.g., reactivity, solubility, mobility, penetration ability, nature of functionalized material, type of metal and organic precursors.…”
mentioning
confidence: 99%